Biventricular Global Function Index Is Associated With Adverse Outcomes in Repaired Tetralogy of Fallot. (August 2021) - Alsaied, Tarek; Geva, Tal; Graf, Julia A.; Sleeper, Lynn A.; Marie Valente, Anne
Abstract : Introduction: Cardiac magnetic resonance (CMR) derived biventricular global function index (BVGFI) is a new CMR parameter that integrates biventricular volumes, mass, and function using clinically available CMR parameters. The associations of BVGFI with clinical outcomes in repaired tetralogy of Fallot are unknown. Methods: Patients with repaired tetralogy of Fallot who had a CMR before the occurrence of a composite outcome of death, resuscitated sudden death, or sustained ventricular tachycardia were studied. BVGFI was calculated as the average of right and left GFI. GFI was defined as (ventricular stroke volume×100)/(ventricular mean cavity volume + total ventricular myocardial volume). Ventricular mean cavity volume was defined as ([end-diastolic + end-systolic volume]/2). Cox multivariable regression analysis and classification and regression tree methodology were used. Results: Of the 736 eligible subjects (mean age at CMR 25.4±14.5 years), with a median follow-up of 28 months, 55 subjects (7.4%) reached the composite outcome (46 deaths and 9 sustained ventricular tachycardia). Independent associations with the composite outcome were as follows: BVGFI <37 (hazard ratio, 2.52; P =0.004), right ventricular end-systolic volume index >85 mL/m 2 (hazard ratio, 3.25; P <0.001), atrial tachycardia (hazard ratio, 2.03; P =0.021), and age at repair >2.5 years (hazard ratio, 3.37; P <0.001). Classification and regression tree analysis identified BVGFI as the most discriminatory CMR parameter associated with a high risk for adverse outcomes. Conclusions: BVGFI, a novel CMR-derived imaging biomarker combining biventricular volumes, mass, and function, may improve risk stratification for adverse clinical outcomes in patients with repaired tetralogy of Fallot.